Early exposure to flame retardants is prospectively associated with anxiety symptoms in adolescents: A prospective birth cohort study. Issue 12 (11th October 2022) - Strawn, Jeffrey R.; Xu, Yingying; Cecil, Kim M.; Khoury, Jane; Altaye, Mekibib; Braun, Joseph M.; Lanphear, Bruce P.; Sjodin, Andreas; Chen, Aimin; Yolton, Kimberly
Abstract: Background: Anxiety disorders emerge during childhood and adolescence and are frequently preceded by subsyndromal anxiety symptoms. Environmental toxicants, including gestational polybrominated diphenyl ether (PBDE) exposure, are associated with neuropsychiatric sequelae; however, the role of PBDEs as risk factors for anxiety in adolescence is unclear. Methods: Using data from the Health Outcomes and Measures of the Environment (HOME) Study, a prospective pregnancy and birth cohort enrolled from 2003 to 2006, we investigated the relationship between gestational serum PBDE concentrations and anxiety symptoms in adolescents ( N  = 236). We measured five PBDE congeners (PBDE‐28, −47, −99, −100, and −153) at 16 ± 3 weeks of gestation and calculated their sum (∑PBDE). We assessed self‐reported anxiety symptoms using the Screen for Child Anxiety Related Emotional Disorders (SCARED) and depressive symptoms using the Children's Depression Inventory (CDI‐2) at age 12 years. We estimated the associations of maternal PBDE concentrations with child anxiety and depressive symptoms using multivariable linear regression and modified Poisson regression. Covariates included child sex, maternal race, maternal age at delivery, maternal marital status, maternal education, and household income at the 12‐year study visit as well as maternal depressive and anxiety symptoms. Sensitivity analyses were performed to control for maternal lead and mercury at delivery. Results: After adjusting for predetermined covariates, each doubling in maternal PBDE concentrations was associated with increased SCARED scores (e.g., for ∑PBDE, SCARED total score, β  = 1.6 95% confidence interval [CI]: 0.3–2.9, p  = .019) and a nonsignificant increase in depressive symptoms (e.g., for CDI total score, β  = .8, 95% CI: −0.2–1.8, p  = .11). Conclusions: Gestational serum PBDE concentrations just before mid‐pregnancy and during a period of active cortical and limbic neurogenesis, synaptogenesis and myelogenesis may be a risk factor for developing anxiety symptoms in early adolescence.